Desain Perancangan Mesin Pemotong Kentang Multifungsi - Rohman, Arif; Saputra, Trisma Jaya; Dewi, Rany Puspita (Rekayasa Material, Manufaktur dan Energi, 2025)
We often encounter potatoes in eating places and restaurants that have been made into ready-to-eat food because they are easy to process into various kinds of food, one of which is french fries. The aim of this research is to produce a design for a multifunctional potato cutting machine that is efficient and portable. The concept refers to the design process of designing a machine by determining the dimensions, size and constituent components displayed on the working drawings. The results of this multifunctional potato cutting machine design resulted in the design of machine components such as a potato funnel hopper with dimensions of 300 mm x 80 mm x 222 mm, a potato pusher with dimensions of 80 mm x 114 mm, and the main frame of the machine with dimensions of 421 mm x 300 mm x 380 mm. Three variations of cutting knives consisting of flat, long/stick-shaped and soft-shaped cutting knives. The knife driver used is an electric motor with a power of 125 watts, blade rotation speed of 700 rpm, and another drive transmission. Overall, the results of this design produce a design drawing for a potato cutting machine with dimensions of 421 mm x 300 mm x 544 mm, so that this machine is more efficient and portable.